Aerodynamic Interaction of Migratory Birds in Gliding Flight - Beaumont, Fabien; Murer, Sébastien; Bogard, Fabien; Polidori, Guillaume (Fluids, 2023)
(1) Background: Many studies suggest that migratory bird groups fly in a V-formation to improve their aerodynamic efficiency, the goal being to reduce their energy expenditure to fly longer distances. To further validate this hypothesis, we numerically simulated the aerodynamic interaction of two gliding migratory birds and evaluated the aerodynamic forces as a function of the bird spacing. (2) Methods: Computational Fluid Dynamics (CFD) was used to model the flow pattern in and around the wake of Canada geese flying at an altitude of 1000 m and a speed of 13.9 m/s. (3) Results: The post-processing of the 3D results revealed a complex flow structure composed of two contra-rotating vortices developing at the wing tip. (4) Conclusions: In a plane perpendicular to the main flow direction, we showed that the bird’s wake could be broken down into two distinct zones: the downwash zone and the upwash zone, the latter being used by birds flying in formation to reduce their energy expenditure. The results of our study suggested an optimal wingtip spacing of -26cm to maximize the lift/drag ratio that characterizes aerodynamic efficiency.
Number: 2
Keywords: computational fluid dynamics (CFD); migratory birds; vortex; wake